A novel TIPT double mutation in EPSPS conferring glyphosate resistance in tetraploid Bidens subalternans. Issue 1 (12th August 2019) - Takano, Hudson K; Fernandes, Vanessa NA; Adegas, Fernando S; Oliveira Jr, Rubem S; Westra, Philip; Gaines, Todd A; Dayan, Franck E
Abstract: BACKGROUND: Bidens subalternans (greater beggarticks) is a tetraploid and troublesome weed infesting annual crops in most tropical regions of the world. A glyphosate‐resistant (GR) B. subalternans biotype was detected in a soybean field from Paraguay. A series of physiological and molecular analyses were conducted to elucidate its resistance mechanisms. RESULTS: The GR biotype had a high level of resistance (> 15‐fold LD50 ), relative to a glyphosate‐susceptible (GS) biotype. Shikimate accumulation was up to ten‐fold greater for GS compared with GR. We found no differences in sensitivity when plants were treated and kept under lower (10/4 °C) or higher temperatures (25/20 °C). GS and GR had the same relative EPSPS gene copy number, and similar glyphosate absorption and translocation rates. Neither biotype metabolized glyphosate. A double amino acid substitution (TIPT – Thr102Ile and Pro106Thr) was found in only one EPSPS allele from one of the two EPSPS homoeologs present in tetraploid GR B. subalternans . CONCLUSION: This is the first report of a TIPT double mutation conferring high levels of glyphosate resistance in a weed species. The presence of both wild‐type and TIPT mutant EPSPS on the polyploid genome of GR B. subalternans may offset a potential fitness cost, requiring additional research to confirm the absence of deleterious effects. © 2019 Society of Chemical Industry Abstract : A double amino acid substitution (TIPT – Thr102Ile and Pro106Thr) in one EPSPS allele from one of the two EPSPS homoeologs confers glyphosate resistance in tetraploid Bidens subalternans .